Experimental Age Discrimination Evidence and the Heckman Critique - Neumark, David; Burn, Ian; Button, Patrick (American Economic Review, 2016)
We design and implement a large-scale field experiment on age discrimination to address limitations of past research that may bias their results. One limitation is the practice of giving older and younger applicants similar experience in the job to which they are applying, to make them “otherwise comparable.” The second limitation is ignoring the likelihood of greater variation in unobserved differences among older workers owing to human capital investment. Based on evidence from over 40,000 job applications, we find robust evidence of age discrimination in hiring against older women, but considerably less evidence of age discrimination against older men.